Hemophagocytic syndrome, a rare variant of Still’s disease - Bhave, Neha; Gupta, Dinesh; Kashyap, Prashant (International Journal of Research in Medical Sciences, 2017)
Adult onset still’s disease is a rare systemic inflammatory disorder of unknown etiology that is responsible for a significant number of cases of fever of unknown origin (FUO) and musculoskeletal diseases. The diagnosis in adult onset still’s disease is mainly clinical and requires exclusion of other infections. Laboratory tests are nonspecific and treatment mainly comprises of corticosteroids, NSAIDS, immunosuppressive drugs, iv gamma globulin, anti-tumour necrosis factor, anti-interleukin. AOSD (adult onset stills disease) is a diagnostic challenge. Discovery of new serological tests and a specific diagnostic criterion may help the clinician in faster diagnosis and better management of the disease.